A receptance-based vibration control with dead-zone compensation for systems with input delay. (1st October 2022) - Duarte, André Juarez Jaime; Santos, Tito Luís Maia; Araújo, José Mário
Abstract: This paper presents a novel compensation approach for receptance-based second-order systems with long input delay and unknown dead-zone input nonlinearity. The approach is based on a filtered Smith predictor for systems with long input delay based on the receptance model. An innovative discrete-time adaptive strategy approach for dealing with unknown input dead-zone is also based on a receptance model realization. The receptance-based second-order model is used on several fundamental applications, including active control vibration of mechanical vibrating systems. In the proposed approach, a filtered prediction error that considers the effects of time delay can be applied to pursue state feedback design for active vibration control purposes. The dead-zone compensation is treated by a discrete-time state observer, which is based on displacement, velocity, and control effort signals to estimate the unknown parameters to be used on an adaptive algorithm. The main contribution of this work is to combine unknown dead-zone adaptive mechanism and a receptance-based time delay compensation in a unified design. Some numerical examples illustrate the effectiveness of the innovative proposed approach. Graphical abstract: Highlights: An approach to dealing with time delay and dead-zone is proposed. An adaptive mechanism is proposed to track the unknown dead-zone parameters. Active vibration control is performed using the proposed approach.